1947
DOI: 10.1007/bf02642129
|View full text |Cite
|
Sign up to set email alerts
|

Hygroscopic equilibrium of cottonseed

Abstract: Summary and Conclusion An investigation has been made of the hygroscopic equilibrium of cottonseed over a range of 31% to 93% relative humidity. From 31% to 71% relative humidity the moisture content of cottonseed increased linearly from 6.03% to 10.27%. From 71% to 93% relative humidity the moisture content increased rapidly from 10.27% to 22.19%. When cottonseed was separated into meats and hulls, including linters, it was found that the hulls contained more moisture than the meats. On the basis of these res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

1950
1950
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…In agreement with our findings for tobacco, the seed-covering layers of many oilseeds are known to have higher water uptake capacities compared to the embryos, e.g. the equilibrium moisture content of the cotton (Gossypium hirsutum) or sunflower (Helianthus annuus) seed-covering layers is approximately 4% higher compared to the embryos (Karon, 1947;Shatadal and Jayas, 1990;Mazza and Jayas, 1991;American Society of Agricultural Engineers, 2001). …”
supporting
confidence: 87%
“…In agreement with our findings for tobacco, the seed-covering layers of many oilseeds are known to have higher water uptake capacities compared to the embryos, e.g. the equilibrium moisture content of the cotton (Gossypium hirsutum) or sunflower (Helianthus annuus) seed-covering layers is approximately 4% higher compared to the embryos (Karon, 1947;Shatadal and Jayas, 1990;Mazza and Jayas, 1991;American Society of Agricultural Engineers, 2001). …”
supporting
confidence: 87%
“…Blue lupine seeds seem to attain equilibrium with humidity of the air more slowly than do many other seeds and grains for which results have been reported (4,9,10,11,12,15). This slower rate of absorption of moisture in the vapor phase is coupled, however, with a higher total uptake than is found in many other seeds.…”
Section: Discussionmentioning
confidence: 79%
“…These seeds showed a slight mold growth, and their relatively high moisture content was no doubt partly attributable to a decrease in seed dry matter due to fungal metabolism or to moisture held by the fungus mycelium itself. Workers using other seeds (4,9,10,11,12,15) figure 2 (B, C) was designed to show the differences between the 6-week and 8-week storage periods in effects on seed-air moisture exchanges throughout the relative humidity range. From the preliminary studies and from these data, it was concluded that naturally dried blue lupine seed apparently requires seven to eight weeks to attain equilibrium with air of high and low relative humidities but not more than six weeks with air of intermediate humidities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1A shows that cottonseed of low initial moisture and free fatty acids contents did not heat. In seed of higher initial moisture and free fatty --nnmn nun 9 acids contents there was an increasing tendency to heat and aeration was required to control the temperature. (See cross hatching at the bottom of the individual graphs in Figure 1.)…”
Section: Effect Of Storage On Seedmentioning
confidence: 99%